Life as an early career researcher: Ruth Bower. (14th July 2016) - Bower, Ruth
Ruth Bower talks to Francesca Lake, Managing Editor: Ruth is currently researching head and neck cancer chemoradiotherapy regimens utilizing microfluidic technology to maintain and interrogate biopsies. Tissue response is investigated using a variety of whole tissue and cellular analytical techniques with a view toward personalized medicine. She is currently pursuing her PhD within the head and neck cancer research group at Hull University (UK). Ruth obtained a first class (Hons) degree in Biological Sciences from Lancaster University (UK) during which time she spent a year at the University of Wollongong (Australia).